Oviposition of Quesada gigas (Hemiptera: Cicadidae) in coffee plants - Decaro Júnior, Sergio T. [UNESP]; Martinelli, Nilza M. [UNESP]; Maccagnan, Douglas H.B.; Ribeiro, Eduardo S.D.B.P. [UNESP] (My University, 2012)
Branches of coffee-plant were collected in São Sebastião do Paraíso County, Minas Gerais State, at the Experimental Station of the Agricultural Research Company (Empresa de Pesquisa Agr opecuária de Minas Gerais - EPAMIG),with the aim of studying various aspects of oviposition by Quesada gigas (Hemiptera: Cicadidae). The number of branches with Q. gigas egg nests was analyzed, as well as the number of nests per branch, the eggs per nest and the diameter of the egg nest location on the branch. The preference for oviposition either on alive or dry branches and the size of the egg were assessed. Egg-laying occurred only on dry branches. The mean of the branch diameter on which the egg nests occurred was 2.5 ± 0.53 mm. The number of eggs per nest averaged 13.2 ± 4.9, and the number of egg nests per branch was 2.2 ± 1.74. The eggs were 1.9 ± 0.08 mm long by 0.5 ± 0.04 mm wide. The largest diameters of the branches containing egg nests were found on the upper third of the trees, as well as the greatest amount of branches with egg nests, of egg nests per branch and of eggs per nest. The correlation relationship between all of the experiment variables was positive.
Oviposición de quesada gigas (hemiptera: Cicadidae) en plantas de café
Keywords: Cicada; Cicadoidea; Coffea arabica; Dry branches; Eggnest